Pengembangan E-Modul Pembelajaran Interaktif Pada Materi Sistem Air Conditioner (Ac) Di Smk Muhammadiyah 3 Yogyakarta - aziz; subagyo; arif bintoro Johan (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2024)
ABSTRACT The objectives of this study are: (1) Develop and produce teaching materials E-module ac system material for class XII majoring in Automotive at SMK. (2) Knowing the feasibility of the E-module. The research method used is Research And Development (R&D) with reference to the 4D development model, namely define, design, development and dissemination. Data collection instruments are in the form of expert validation questionnaires and student questionnaires. Data analysis techniques use quantitative descriptive analysis techniques. The results of the analysis of material expert lecturers got 94.4% with the classification of